STRATEGI PEMBENTUKAN JIWA KEWIRAUSAHAAN BAGI MAHASISWA UNTUK MEWUJUDKAN PELAKU UMKM MANDIRI - Zarkasi, Zarkasi (JURNAL ILMIAH EDUNOMIKA, 2024)
Students, as Agents of Change from an early age, must have an extensive understanding of the importance of progress in the business field, including strengthening the entrepreneurial spirit. Various parties, including higher education, must support entrepreneurship. This will, in turn, produce independent entrepreneurs and micro, small, and medium-sized enterprises (UMKM) players who are driven by the attitudes and characteristics of entrepreneurs and ready to persevere and develop the business world in the future. Various strategies used to foster entrepreneurs and UMKM players in higher education are crucial to be carried out systematically and continuously. This article aims to: 1) Provide an overview of strategies for creating an entrepreneurial spirit in students and its relevance to the realization of independent UMKM. 2) Provide contributions, suggestions, and solutions to parties involved in the entrepreneurial spirit of students to become the foundation for the establishment of independent UMKM. This article concludes that: 1) There are several strategies used to create the entrepreneurial spirit of students, namely by providing motivation and understanding related to entrepreneurial characteristics, such as being action-oriented, thinking simply, seeking new opportunities, pursuing opportunities with high discipline, seizing the best opportunities, focusing on execution and everyone's energy into the business they are engaged in, and real strategies that can be implemented in higher education include achieving learning outcomes in the curriculum, participating in Student Creativity Programs (PKM), and establishing business incubators. 2) To contribute suggestions and solutions to the issue of UMKM self-sufficiency, several steps need to be taken. First, change the lifestyle from dependence on imported goods. Second, change government policies and attitudes towards UMKM. Third, the UMKM sector needs assistance in finding better production inputs, suitable technology, efficient marketing strategies, and services. Fourth, UMKM must improve their knowledge and skills. Fifth, the UMKM sector needs easier access to financing, which often becomes a source of problems inhibiting its growth. Sixth, the government must remove various barriers that hinder the growth and expansion of the UMKM sector.